2014
DOI: 10.1111/1750-3841.12374
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids, but Not Vitamin A, Improve Iron Uptake and Ferritin Synthesis by Caco‐2 Cells from Ferrous Fumarate and NaFe‐EDTA

Abstract: Due to the high prevalence of iron and vitamin A deficiencies and to the controversy about the role of vitamin A and carotenoids in iron absorption, the objectives of this study were to evaluate the following: (1) the effect of a molar excess of vitamin A as well as the role of tannic acid on iron uptake by Caco-2 cells; (2) iron uptake and ferritin synthesis in presence of carotenoids without pro-vitamin A activity: lycopene, lutein, and zeaxantin; and (3) iron uptake and ferritin synthesis from ferrous fumar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…b-Carotene and vitamin A improved iron absorption in vivo [36,37], but only b-carotene did so in vitro as well [38]. Vitamin A failed to enhance iron absorption in humans [39] and in Caco-2 cells [38]. It seems, from the literature, that b-carotene is a more potent enhancer of iron bioavailability, in accordance with the present observations.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…b-Carotene and vitamin A improved iron absorption in vivo [36,37], but only b-carotene did so in vitro as well [38]. Vitamin A failed to enhance iron absorption in humans [39] and in Caco-2 cells [38]. It seems, from the literature, that b-carotene is a more potent enhancer of iron bioavailability, in accordance with the present observations.…”
Section: Discussionsupporting
confidence: 82%
“…Anti-inflammatory effects of vitamin A have been reported [35]. b-Carotene and vitamin A improved iron absorption in vivo [36,37], but only b-carotene did so in vitro as well [38]. Vitamin A failed to enhance iron absorption in humans [39] and in Caco-2 cells [38].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, moringa contained the highest number of enhancers of iron absorption: β-carotene [ 7 , 8 ] and ascorbic acid [ 44 ]; although in this study their effect were not realised except for the concentration of iron. Additionally, the concentration of total polyphenols in this DGLV was moderate.…”
Section: Discussionmentioning
confidence: 63%
“…In a human feeding trial conducted by Garcia-Casal and co-workers [ 7 ], it was found that β-carotene enhances iron absorption when added to cereal-based diets. This finding was confirmed using Caco-2 cells as a model for iron availability [ 8 ]. Thus, the consumption of these greens, reported to be rich in micronutrients such as β-carotene [ 9 , 10 ], should have a double impact as a provitamin A dietary source, and also as an enhancer of iron absorption.…”
Section: Introductionmentioning
confidence: 61%
“…The significantly lower chelating of PO than RPO might due to the removal of carotene compounds from RPO during bleaching process and the lower vitamin E content than RPO 3 and 5) . Previous studies on iron uptake by human colorectal adenocarcinoma cells, Caco-2 showed that carotenoids significantly increased iron uptake from ferrous fumarate and NaFe-EDTA, and were capable of partially overcoming the inhibition produced by tannic acid 72) . Thus, the weaker activities shown by the oil extracts in the FIC assay is possibly due to lack of the carotenoids that are efficient in ferrous ion binding activity.…”
Section: Resultsmentioning
confidence: 96%